Auditoría de gestión al departamento de talento humano y su incidencia en la eficiencia y eficacia de la empresa “corp naula s.a.s.” año 2021 - Laje Moncada , Lady Xilena (2022)
The main objective of this research work is to evaluate the incidence of the management audit of the Human Talent department in the efficiency and effectiveness of the Naula S.A.S corporation, year 2021, related to the fulfillment of the company's objectives. methodology that was improved was the explanatory and descriptive one, during the development of this research project, interviews and surveys were shown to company officials, the application of management indicators and the evaluation of internal control helped to identify, which indicate non-compliance with the current regulations of the labor code, the application of an empirical selection and recruitment process, the absence of function manuals, through the evaluation of internal control, the level of trust and risk of the company will be extended, the application of the management indicators were known the levels of efficiency and effectiveness of the personnel that work in the entity and the human talent department.